2013
DOI: 10.4067/s0716-10182013000500003
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus coagulasa-negativa clínicamente significativos: Especies más frecuentes y factores de virulencia

Abstract: The frequency of S. lugdunensis, the most virulent coagulase-negative staphylococci species, was relatively high. The main virulence factor in S. epidermidis was biofilm production, being higher in those resistant to methicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
4
0
10
Order By: Relevance
“…Of all known pathogenic Vibrio of major medical interest listed by Daniels and Shafaie (2000), only V. parahaemolyticus was present in our oyster samples. Among those isolated from surface waters, the coagulase-negative Staphylococcus warneri and S. cohnii are of mild clinical interest as possible sources of nosocomial infections (Martínez and Máttar 2006, Fariña et al 2013, Soldera et al 2013, while Lysobacter spongiicola pertains to a genus of potential importance for its production of several extracellular enzymes (de Bruijn et al 2015), and because several Lysobacter species have been suggested for biological plant disease control (Hashizume et al 2004, Li et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Of all known pathogenic Vibrio of major medical interest listed by Daniels and Shafaie (2000), only V. parahaemolyticus was present in our oyster samples. Among those isolated from surface waters, the coagulase-negative Staphylococcus warneri and S. cohnii are of mild clinical interest as possible sources of nosocomial infections (Martínez and Máttar 2006, Fariña et al 2013, Soldera et al 2013, while Lysobacter spongiicola pertains to a genus of potential importance for its production of several extracellular enzymes (de Bruijn et al 2015), and because several Lysobacter species have been suggested for biological plant disease control (Hashizume et al 2004, Li et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance remains a major threat to public health worldwide (10). Although other studies showed that the most prevalent spices was S. epidermidis (11,12), the results of the present study showed that S. hominis and S. haemolyticus, as the most important causes of nosocomial infections, had the highest prevalence (10). Insufficient hand hygiene and inadequate disinfection and/or sterilization of medical instruments and surfaces may also be assumed as causes of the distribution of coagulase-negative Staphylococci (CoNS) such as S. hominis and S. haemolyticus in the hospital settings (13).…”
Section: Discussionmentioning
confidence: 99%
“…La prueba de sensibilidad antimicrobiana se hizo siguiendo el método de difusión en disco Kirby-Bauer. Se hizo una dilución bacteriana semejante a la escala de turbidez de 0.5 de McFarland y la muestra fue sembrada en el agar Müller-Hinton con la ayuda de un hisopo estéril (Fariña et al, 2013). Se seleccionaron los antibióticos más usados en la clínica de animales de compañía para el tratamiento de otitis externa.…”
Section: Susceptibilidad Antimicrobianaunclassified